2014
DOI: 10.1007/s40265-014-0271-z
|View full text |Cite
|
Sign up to set email alerts
|

OnabotulinumtoxinA (Botox®): A Review of its Use in the Treatment of Urinary Incontinence in Patients with Multiple Sclerosis or Subcervical Spinal Cord Injury

Abstract: OnabotulinumtoxinA (BOTOX(®)) is a type A neurotoxin derived from Clostridium botulinum bacteria that is approved as treatment for urinary incontinence (UI) in patients with neurogenic detrusor overactivity resulting from multiple sclerosis (MS) or subcervical spinal cord injury (SCI) who are not adequately treated by antimuscarinics. This article reviews the pharmacology of intradetrusor onabotulinumtoxinA in this indication. The presumed mode of action of onabotulinumtoxinA in bladder disorders is by interfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Approved by the U.S. Food and Drug Administration for the treatment of neurogenic bladder dysfunction in 2011, it is injected into the bladder using a cystoscope. 39 The effect lasts 6 to 12 months, at which point another injection is required. The treatment carries a risk of urinary retention, which would require short-term CIC.…”
Section: Failure To Storementioning
confidence: 99%
“…Approved by the U.S. Food and Drug Administration for the treatment of neurogenic bladder dysfunction in 2011, it is injected into the bladder using a cystoscope. 39 The effect lasts 6 to 12 months, at which point another injection is required. The treatment carries a risk of urinary retention, which would require short-term CIC.…”
Section: Failure To Storementioning
confidence: 99%
“…Carneiro et al reported the efficacy of botulinum toxin type A for HAM/TSP‐associated OAB refractory to conventional drug in 3 patients. Botulinum toxin type A, a neuromuscular blocking agent, has been used to treat neurogenic OAB following detrusor overactivity in patients with multiple sclerosis and spinal cord injury . Botulinum toxin type A is usually injected intravesically and is an invasive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Botulinum toxin is an invasive technique which has similar efficacy to sacral neuromodulation (SNM) in NOAB; improvement rates of 63.5% for Botox and 58.5% for SNM have been reported . Moreover in studies which evaluated the effect of botulinum toxin in NOAB, it has been suggested that it is a clinically important advance in the therapy of urinary incontinence in patients with MS or spinal cord injury (SCI) who have not responded to antimuscarinics or who are unable to tolerate antimuscarinics . In another study, it was reported that botulinum toxin treatment has beneficial effects not only on urinary symptoms but also on QoL, in patients with SCI and MS .…”
Section: Discussionmentioning
confidence: 99%